2012
DOI: 10.2169/internalmedicine.51.6555
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of a Mesangial Proliferative Glomerulonephritis with Interstitial Nephritis Associated with Castleman's Disease by an Anti-interleukin-6 Receptor Antibody (Tocilizumab)

Abstract: We report a case of mesangial proliferative glomerulonephritis with interstitial nephritis associated with multicentric Castleman's disease (MCD) successfully treated with an anti-interleukin-6 receptor antibody (tocilizumab). This mesangial proliferative glomerulonephritis with interstitial nephritis was resistant to methylprednisolone treatment; however, it was markedly improved with tocilizumab, which was administered intravenously at a dose of 8 mg/kg every 2 weeks. These results suggest that tocilizumab i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Normal levels of IL-6 expression are conducive to immunological homeostasis, whereas excessive production can cause a series of inflammatory lesions, leading to such diseases as rheumatoid arthritis, Crohn’s disease, and glomerulonephritis. 26 28 Transgenic mice overexpressing IL-6 developed a variety of disorders, including pulmonary fibrosis, hypertension, multiple myeloma, plasmacytosis, and neurological disease. 29 31 …”
Section: Introducing Il-6mentioning
confidence: 99%
“…Normal levels of IL-6 expression are conducive to immunological homeostasis, whereas excessive production can cause a series of inflammatory lesions, leading to such diseases as rheumatoid arthritis, Crohn’s disease, and glomerulonephritis. 26 28 Transgenic mice overexpressing IL-6 developed a variety of disorders, including pulmonary fibrosis, hypertension, multiple myeloma, plasmacytosis, and neurological disease. 29 31 …”
Section: Introducing Il-6mentioning
confidence: 99%
“…Therefore, we sought to identify the cytokines and/or chemokines responsible for the development of RPGN in SCG/Kj mice by using a microsphere‐based multiplex protein assay, and to investigate their clinical potential as a target of monoclonal antibody therapy. A monoclonal antibody against IL‐6R, tocilizumab, has been used to treat inflammatory diseases such as Castleman disease , systemic juvenile idiopathic arthritis , and RA . Because the IL‐6 signaling pathway plays an important role in autoantibody production, it should be studied in relation to MPO–ANCA production in SCG/Kj mice.…”
mentioning
confidence: 99%
“…Second, TCZ treatments cannot always eliminate renal amyloid deposits in patients with AA amyloidosis. Recent case reports have revealed that TCZ treatments decrease proteinuria and improve or preserve renal function in patients with renal AA amyloidosis [8, 1214]; however, the present patient's renal involvement was refractory to TCZ treatment.…”
Section: Discussionmentioning
confidence: 59%